Stability Of Underground Openings Adjacent To The Sink Hole At The NIOSH Lake Lynn Research Laboratory - D. R. Dolinar; T. E. Marshall; T. M. Barczak; T. P. Mucho (The National Institute for Occupational Safety and Health (NIOSH))
Over a portion of the older limestone mine workings at the NIOSH Lake Lynn Laboratory, a mining health and safety research facility, a large sinkhole formed caused in part by the intersection of several tightly spaced joint sets and unusual weather conditions. The anticipated propagation of the associated roof failures threatened to encroach upon a portion of the facility’s secondary escapeway. To protect the escapeway, two cribs walls and over 80 cable bolts were installed. In addition, extensometers were installed to monitor roof movement in the escapeway. However, a large roof fall associated with the propagating roof failures in the sinkhole area partially destroyed one crib wall where the adjacent escapeway was not reinforced by cable bolts. Recent roof movement information indicates that this area is still active. Based on these measurements, steps have been taken to stabilize this portion of the escapeway. This paper discusses roof monitoring, the roof movement, the large roof fall, propagation of the roof failures, and the recent support measures undertaken to stabilize the escapeway.